Cryopreserving cultured cells - Morrey, John D; Lowry, William (Utah : Taped Technologies, 1992)
Experiments and demonstarating the techniques of preserving cell culture. THe steps are includes making cryopreservation / thaw media, preparing cells for freezing, dispensing cells in cryovials, sealing glass cryovials, freezing cells and thawing cells.
Keywords: Cells -- Cryopreservation; Cell culture